Isolation and characterization of a novel lytic phage K14-2 infecting diverse species of the genus Klebsiella and Raoultella - Kang, Seomin; Han, Jeong-Eun; Choi, Young-Sik; Jeong, In-Chul; Bae, Jin-Woo (Frontiers in Microbiology, 2025)
Multi-drug-resistant bacteria pose a significant global threat to public health, particularly among patients with critical nosocomial infection. Notably, the genera Klebsiella and Raoultella are of concern due to their association with human infections and the transfer of antibiotic-resistance genes. Phage therapy has recently garnered attention as a novel approach to treating these infections. However, the efficacy of this method relies on phages with a broad host range. In this study, the phage K14-2 with a wide host range was isolated from a river water sample using Klebsiella pneumoniae as the host. The biological properties of the phage were characterized by assessing its multiplicity of infection, killing curve, one-step growth curve, and stability across different pH levels and temperatures. The morphological analysis revealed that the phage closely resembled myovirus. The host range included 15 strains across 6 species from Klebsiella, Raoultella, and Escherichia genera. The genome of K14-2 was found to be double-stranded DNA, comprising 175,759 base pairs with a GC content of 41.8%. Genome annotation revealed 280 protein-coding genes, of which 96 had assigned functions. The phage with the highest genomic similarity to K14-2 was vB_KpM-Milk. Phylogenetic trees constructed based on the major capsid protein revealed that the phage belonged to the genus Slopekvirus of the Straboviridae family. Given these characteristics, the discovery of the novel phage K14-2, with its broad host range, holds potential for enhancing the effectiveness of phage therapy in future studies.